Potentially Suboptimal Prescribing for Older Veteran Nursing Home Patients With Dementia. (January 2015) - Hanlon, Joseph T.; Aspinall, Sherrie L.; Handler, Steven M.; Gellad, Walid F.; Stone, Roslyn A.; Semla, Todd P.; Pugh, Mary Jo V.; Dysken, Maurice W.
Background: Nursing home patients with dementia may be more likely to suffer adverse drug events from suboptimal prescribing. Previous studies have not used national samples, nor have they examined multiple types of suboptimal prescribing by dementia severity.Objective: To examine the prevalence of and factors associated with potentially suboptimal prescribing in older veteran nursing home patients with dementia.Methods: This is a retrospective descriptive study of 1303 veterans 65 years or older admitted between January 1, 2004, and June 30, 2005, with dementia for long stays (90+ days) to 133 Veterans Affairs Community Living Centers. Dementia severity was determined by the Cognitive Performance Scale and functional status dependences.Results: Overall, 70.2% with mild-moderate dementia (n = 1076) had underuse because they did not receive an acetylcholinesterase inhibitor (AChEI), and 27.2% had evidence of inappropriate use because of a drug-disease or drug-drug-disease interaction. Of the 227 with severe dementia, 36.1% had overuse by receiving an AChEI or lipid-lowering or other agents, and 25.1% had evidence of inappropriate use as a result of a drug-disease or drug-drug interaction. Multinomial logistic regression analyses among those with mild to moderate dementia identified that living in the South versus other regions was the single factor associated with all 3 types of suboptimal prescribing. In those with severe dementia, antipsychotic use was associated with all 3 suboptimal prescribing types.Conclusions: Potentially suboptimal prescribing was common in older veteran nursing home patients with dementia. Clinicians should develop a heightened awareness of these problems. Future studies should examine associations between potentially suboptimal prescribing and health outcomes in patients with dementia.